Global Variations in the Mineral Content of Bottled Still and Sparkling Water and a Description of the Possible Impact on Nephrological and Urological Diseases - ŞENER, TARIK EMRE (MDPI, 2021)
Kidney stone disease (KSD) is a complex disease. Besides the high risk of recurrence, its association with systemic disorders contributes to the burden of disease. Sufficient water intake is crucial for prevention of KSD, however, the mineral content of water might influence stone formation, bone health and cardiovascular (CVD) risk. This study aims to analyse the variations in mineral content of bottled drinking water worldwide to evaluate the differences and describes the possible impact on nephrological and urological diseases. The information regarding mineral composition (mg/L) on calcium, bicarbonate, magnesium, sodium and sulphates was read from the ingredients label on water bottles by visiting the supermarket or consulting the online shop. The bottled waters in two main supermarkets in 21 countries were included. The evaluation shows that on a global level the mineral composition of bottled drinkable water varies enormously. Median bicarbonate levels varied by factors of 12.6 and 57.3 for still and sparkling water, respectively. Median calcium levels varied by factors of 18.7 and 7.4 for still and sparkling water, respectively. As the mineral content of bottled drinking water varies enormously worldwide and mineral intake through water might influence stone formation, bone health and CVD risk, urologists and nephrologists should counsel their patients on an individual level regarding water intake.
Keywords: kidney stone disease; mineral water; mineral composition; drinking water; still water; sparkling water; CHRONIC KIDNEY-DISEASE; CARDIOVASCULAR-DISEASE; IDIOPATHIC HYPERCALCIURIA; DRINKING-WATER; STONE DISEASE; TAP WATER; CALCIUM; RISK; DIETARY; SODIUM